ANALISIS EVALUASI BAHAN PUSTAKA DALAM KEGIATAN PENGEMBANGAN KOLEKSI DI UPT PERPUSTAKAAN UNIVERSITAS DIAN NUSWANTORO SEMARANG - Hafidzatul Wahidah (Central Library of Universitas Sebelas Maret, 2017)
Evaluation in the collection development aims to assess the strengths and weaknesses of the collection so that the collection provided in accordance with user needs. This study aims to reveal the evaluation activities conducted at UPT Dian Nuswantoro University Library Semarang. The research method used, that is descriptive-qualitative, with data collection method with literature study, interview and observation. The results showthat evaluation process involve librarians, specialist subjects, lecturers and faculty staff. Collection evaluation is done by librarian to make list of book collection to be evaluated, then given to lecturer for ACC and chosen to be evaluated and weeded. Recommendations for this library are time management and optimization of the use of Information and Communication Technology (ICT) in the evaluation process in the development of collections.